Russian-Chinese relations since the end of the bipolar world - Bastova, Vita; Maslowski, Nicolas, 1972-; Cibulková, Petra, 1977-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2013)
Russian-Chinese relations have been differed by the complex and full relations, which have been highly emerged since the end of the Cold War. Transition of the power in the world system had overcome the intention of Russia and China for the closer cooperation in order to decline the American sole hegemony. Concluding the Friendship treaty, it had become the first step towards cooperation which today can be considered as stable one. Master thesis will be focused on the realist approach, which at the same time will help to evaluate Rusian-Chinese relation through the pragmatic realist prism. Analyzing the relations in a global context within further movement to regional one, I will try to experience Sino-Russian relations through different approaches and relying on the balance of power theory. Description of the strategic partnership, supported by the multipolar world view and multilateral diplomacy as the tool for the national interests promotion, the research will move towards bilateral modes estimating security, political and economic relations. All in all, the conclusion will be made in order to predict the future of the Russian-Chinese relations and results which both countries have achieved by now.
Vedoucí práce: Nicolas Maslowski
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses